2017
DOI: 10.1007/s00464-017-5943-9
|View full text |Cite
|
Sign up to set email alerts
|

Sep70/Pepsin expression in hypopharynx combined with hypopharyngeal multichannel intraluminal impedance increases diagnostic sensitivity of laryngopharyngeal reflux

Abstract: The identified Sep70/Pepsin ratio may serve as a reliable biomarker for the diagnosis of LPR. As a result, this may help identify additional patients who have a false-negative HMII result due to the 24-h testing window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…[11][12][13][14] The diagnostic approach of LPR is still controversial but many physicians agree with the consideration of multichannel intraluminal impedance-pH monitoring (MII-pH) as the best diagnostic tool. [15][16][17][18] However, MII-pH is not available in many centers and less used among the otolaryngologists. 19 The majority of physicians used clinical tools such as reflux symptom index (RSI) or reflux finding score (RFS) 20,21 which are still criticized regarding the lack of reliability and the lack of consideration of many LPRrelated symptoms and findings.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The diagnostic approach of LPR is still controversial but many physicians agree with the consideration of multichannel intraluminal impedance-pH monitoring (MII-pH) as the best diagnostic tool. [15][16][17][18] However, MII-pH is not available in many centers and less used among the otolaryngologists. 19 The majority of physicians used clinical tools such as reflux symptom index (RSI) or reflux finding score (RFS) 20,21 which are still criticized regarding the lack of reliability and the lack of consideration of many LPRrelated symptoms and findings.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary bile acid is one of the indexes to evaluate LPRD grade[ 34 ]. Hoppo et al [ 35 ] believed that Sep70 was a predictive indicator, and the absence of Sep70 meant that hypopharyngeal cells were damaged. In addition, the Sep70/pepsin ratio can be used to predict LPRD damage with a sensitivity of over 90%.…”
Section: Clinical Features and Diagnosis Of Lprdmentioning
confidence: 99%
“…Salivary bile acid > 1 µmol/L is a reliable indicator to evaluate the severity of LPRD. Hoppo et al [72] suggested that Sep70 is a "protective" indicator, and its absence indicates hypopharyngeal cell damage. The Sep70/pepsin ratio may be a more reliable indicator to reflect the actual damage of LPRD, with a sensitivity as high as 91%.…”
Section: Research and Application Of Reflux Substances As Detection Indicatorsmentioning
confidence: 99%